Pernikahan Rungal Persfektif Hukum Islam: Studi Kasus Masyarakat Desa Kebarongan, Kecamatan Kemrajen, Kabupaten Banyumas - Taufik Taufik; Kharis Mutaqin (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2023)
Rungal marriages or a marriage that step over the elder sibling has become a tradition in Kebarongan Village. The effects emerge not only for the brides but also for the elder siblings, and their families believed it may cause calamity. The people’s negative view for the rungal brides has also created another fear; therefore, “uang pelangkah” is needed to avoid this calamity. Although this tradition is no longer done by many people, people in Kebarongan Village still do this tradition. How is fiqh perspective? Previous studies on rungal marriage have not discussed this from fiqh perspective. Based on the study of fiqh, rungal marriage and “uang pelangkah” belongs to 'urf. The type of 'urf is based on the scope, material and the perspective of the rungal marriage practitioners, whether it is good or bad. In terms of the scope of its use, the rungal tradition and the step money are included in the 'urf khas category. In terms of material, including 'urf fi'li. And in terms of good and bad, it can include 'urf fasid or 'urf shahih depending on the goals and views of the perpetrator in giving step money in marriage.